Nurse prescribing : principles and practice - Courtenay, Molly (Greenwich Medical Media, 1999)
"Nurses working within the expanded role of prescriber will frequently be faced with prescribing decisions. This text provides easily accessible information upon which to base these decisions, ensuring safe and effective prescribing practices. Each chapter examines the different groups of preparations listed in the Nurse Prescribers' Formulary (NPF). Information including product dosage, contraindications, side-effects, drug interactions and specific nursing points is presented in detail. This text is unique, however, in that the reader is also provided with key background information from the relevant life sciences, as it applies to modern clinical practice."--Jacket